Measures of obliviousness and disarming obliqueness in Anna Burns' Milkman. Issue 7 (3rd July 2022) - Malone, Patricia
ABSTRACT: In this essay, I explore the techniques by which Burns uses and explodes the myth of the unspeakable through the deployment of a picaresque mode that enables an ethical trauma narrative. I demonstrate how Burns' work refutes an 'event-based' reading of trauma and discuss how the narrative of Milkman enacts the difficulty of finding vocabulary with which to make traumatic experience intelligible. I suggest that the novel enacts a refusal of suspicious reading by insisting on the authority of its narrator and her capacity to name harm, which instantiates belief as the primary ground of reader reception. This is linked to the possibility of re-thinking trauma narrative in the public sphere and to articulating the specificity of gender-based violence. Modifying the received wisdom of the field of trauma studies associated with Judith Herman, Cathy Caruth, and others, I expand on Clare Hutton's sensitive reading of the specificity of language in the novel to demonstrate the significance of reading Milkman as a novel of voice, per Peter Boxall's work, and illuminate the connection between Milkman and work by Rita Felski and other feminist theorists through discussion of the significance of the aesthetic or 'literary' quality within the telling of trauma.